Pertumbuhan dan Cadangan Karbon Tegakan Rubroshorea leprosula Miq. Di Hutan Penelitian Gunung Dahu, Bogor: Growth and Carbon Stock of Rubroshorea leprosula Miq. in Gunung Dahu Research Forest, Bogor - Cheryn Kania; Prijanto Pamoengkas; Wahyu Catur Adinugroho (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Plantation forests play a role in mitigating climate change through biomass carbon storage influenced by planting distance. This study aims to analyze the effect of planting distance on the growth and carbon stocks of R. leprosula Miq. with planting years 1997 and 1998 and planting distances of 2m × 2m, 3m × 3m, and 4m × 4m in the Gunung Dahu Research Forest, Bogor. The parameters observed included diameter, height, basal area, stand density, crown density, and carbon stocks, analyzed using analysis of variance (95%). The results showed that planting distance had a significant effect (p < 0.05) on diameter, height, stand density, and crown density. The highest diameter was 47.60 cm at 4m × 4m in 1997 and the lowest was 20.91 cm at 2m × 2m. The highest height at 4m × 4m in 1998 was 22.24m and the lowest was 16.05 m. The highest individual density at 2m × 2m in 1997 was 761.67 ind/ha and the lowest at 4m × 4m was 166.67 ind/ha. The highest canopy density value was at a planting distance of 4m × 4m. Meanwhile, the carbon stock parameter showed results that were not significantly different with the three planting distances, the value ranged from 126.44-158.17 tons C/ha, this indicates compensation between tree size and number of trees per unit area